Outcomes Assessment of Sustainable and Innovatively Simple Lifestyle Modification at the Workplace-Drinking Electrolyzed-Reduced Water (OASIS-ERW): A Randomized, Double-Blind, Placebo-Controlled Trial - Young Ah Choi; Dong Hyeon Lee; Doo-Yeoun Cho; Yong-Jae Lee (MDPI AG, 2020)
Oxidative stress has been associated with many diseases as well as aging. Electrolyzed-reduced water (ERW) has been suggested to reduce oxidative stress and improve antioxidant potential. This study investigated the effects of drinking ERW on biomarkers of oxidative stress and health-related indices in healthy adults. We conducted a randomized, double-blind, placebo-controlled clinical trial on 65 participants, who were allocated into two groups. Of these, 61 received intervention (32 with ERW and 29 MW [mineral water]). All participants were instructed to drink 1.5 L/day of ERW or MW for eight weeks. Biomarkers of oxidative stress and health-related indices were assessed at baseline as well as after 4 weeks and 8 weeks of intervention. Of the primary outcome variables assessed, diacron-reactive oxygen metabolites (d-ROMs) and biological antioxidant potential showed a significant interaction between the groups and time, with d-ROMs levels significantly decreased at 8 weeks in ERW compared to those in MW. Among the secondary outcome variables, total, visceral, and subcutaneous fat mass significantly changed over time, with a significant association observed between the group and time. Thus, daily ERW consumption may be a potential consideration for a sustainable and innovatively simple lifestyle modification at the workplace to reduce oxidative stress, increase antioxidant potential, and decrease fat mass.